2019
DOI: 10.1002/slct.201803507
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis of Ag(I) and Organo‐N‐heterocyclic Carbenes: One‐Pot Synthesis of New Anticancer Spirooxindole‐1,4‐dihydropyridines

Abstract: Ag(I)/organo‐NHC catalyst pair (Lewis acidic/basic) delivered from labile Ag(I)‐NHC complex in ethanol has shown synergistic effect to catalyze the one‐pot four‐component reaction of isatins, malononitrile, cyclic ketones and ammonium acetate to produce new series of spirooxindole‐1,4‐dihydropyridine scaffolds. Carbene trapping from pre‐synthesized Ag(I)‐NHC in the form of zwitterionic CS2‐NHC adduct in ethanol provides evidence for the proposed synergistic catalysis. Besides, preliminary results of anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 158 publications
0
6
0
Order By: Relevance
“…Ag(I)‐NHCs are air‐stable and exhibit an equilibrium between neutral and ionic structures in solution. This methodology allowed the researchers to develop a methodology with good reaction scopes (15 examples), short reaction times under mild reaction conditions, affording the spirooxindole‐1,4‐dihydropyridines in good yields [174] . In summary, the authors suggested that there is condensation of the cyclic ketone with ammonium acetate to form an enamine that undergoes Michael reaction with the isatylidene malononitrile derivatives (the Knoevenagel condensed product) to form an adduct that after heterocyclization and subsequent tautomerism affords the desired spirooxindole derivatives (Scheme 91).…”
Section: Spirooxindole Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ag(I)‐NHCs are air‐stable and exhibit an equilibrium between neutral and ionic structures in solution. This methodology allowed the researchers to develop a methodology with good reaction scopes (15 examples), short reaction times under mild reaction conditions, affording the spirooxindole‐1,4‐dihydropyridines in good yields [174] . In summary, the authors suggested that there is condensation of the cyclic ketone with ammonium acetate to form an enamine that undergoes Michael reaction with the isatylidene malononitrile derivatives (the Knoevenagel condensed product) to form an adduct that after heterocyclization and subsequent tautomerism affords the desired spirooxindole derivatives (Scheme 91).…”
Section: Spirooxindole Derivativesmentioning
confidence: 99%
“…Dinuclear Zn [45] CuI/DBU [51] CuSO 4 .5H 2 O [54] , [55] , [59] chiral guanidine/CuI [191] Ag(I)‐NHC complex [174] …”
Section: Spirooxindole Derivativesmentioning
confidence: 99%
“…Balaboina and his colleagues (Balaboina et al, 2019) have prepared spiro oxindole-hydroquinolines (90), which paves a contemporary pathway for the drugs against cancer cells employing a single-pot method aside from Ag(I) and organo-N-heterocyclic carbenes used as a catalyst. This new catalyst was a progeny from labile Ag(I)-NHC in ethanol; therefore, it accommodates acidic Ag(I) alongside a basic NHC.…”
Section: Miscellaneous Catalystsmentioning
confidence: 99%
“…Such properties include calcium channel blocking, anti-mycobacterial, antioxidant, anti-dyslipidemic, Alzheimer's disease, and antidiabetic activities (Kumar et al, 2010;Sirisha et al, 2011;Niaz et al, 2015;Schaller et al, 2018;Malek et al, 2019). Because of the growing reputation of dihydropyridines in the pharmaceutical field, numerous MCRs have been designed to synthesise 1,4-dihydropyridine scaffolds by utilising various heterogeneous catalysts (da Costa Cabrera et al, 2019;Rajesh et al, 2013;Mahinpour et al, 2018;Heydari et al, 2016;Bhaskaruni et al, 2017;Balaboina et al, 2019). Thus, the new MCRs with green protocols have drawn considerable interest, mainly in organic synthesis, drug development, and material science areas with green approaches using effective recyclable heterogeneous catalysts, sustainable procedures with remarkable atom, and carbon efficiency as added benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Dihydropyridines are well known for their calcium channel blocking activity [10] . However, off‐lately, anticancer properties of 1,4‐DHP derivatives have attracted a great deal of interest among medicinal chemists [11–15] . There are very few articles reported that discuss their anticancer activity.…”
Section: Introductionmentioning
confidence: 99%